2019
DOI: 10.1111/tan.13677
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐199a‐3p modulates the function of dendritic cells involved in transplantation tolerance by targeting CD86

Abstract: Dendritic cells (DCs) are key components of the immune system, serving as antigen‐presenting cells to activate adaptive immunity. Whereas mature DCs promote immune responses, immature DCs induce or maintain immunological tolerance by downregulating T‐cell responses. Therefore, DCs are potent antigen (Ag)‐presenting cells in the immune system. MicroRNAs are noncoding RNAs that posttranscriptionally regulate mRNA by binding the 3′‐untranslated region (UTR) of these molecules, modulating their expression. Many re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…There are no reports on miRNAs that regulate CD30, CD40, or CD86 and that have an inversed expression pattern in cHL [ 119 , 120 ]. However, a miRNA-dependent regulation of TNF-α has been shown for miR-130a-3p which is downregulated in cHL, supporting a potential role for this miRNA [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are no reports on miRNAs that regulate CD30, CD40, or CD86 and that have an inversed expression pattern in cHL [ 119 , 120 ]. However, a miRNA-dependent regulation of TNF-α has been shown for miR-130a-3p which is downregulated in cHL, supporting a potential role for this miRNA [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that miR-199b-3p expression was increased in septic acute kidney injury models, and that miR-199b-3p binds to nuclear factor erythroid 2-related factor (NRF2), which is a transcription factor directly involved in the transcriptional activation of genes involved in cellular antioxidant responses that plays a central role in the pathogenesis of TB [ 44 , 45 ]. Furthermore, miR-199a-3p can mediate immune tolerance by regulating dendritic cells, leading to increased secretion of interleukin 10 as well as to the inhibition of the phosphatidylinositol 3-kinase/protein kinase B/nuclear factor kappa B pathway, and miR-16 was significantly upregulated in the serum of patients with TB compared with healthy controls [ 46 , 47 ]. In addition to miR-199b-3p and miR-199a-3p, other miRNAs have also been found to function as major components in cancer biology.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cytokines related to T-cell activation, IFN-γ and IL-2, had a maximum secretion peak at the most prolonged time evaluated, similarly to the CD86 and ICOS-L expression. This differential kinetic expression could be explained by other reported biological mechanisms affecting protein expression, such as post-translational modifications and miRNA regulation, which should be addressed further to explain the B7 dynamic expression [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%